Type B adverse drug reactions reported by an immunoallergology department - Costa MJ; Herdeiro MT; Polónia JJ; Ribeiro-Vaz I; Botelho C; Castro E; Cernadas J. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: Characterization of the adverse drug reactions (ADR) reported by the immunoallergology department (IAD), Centro Hospitalar de São João (Porto), to the Northern Pharmacovigilance Centre (NPC). Methods: An observational, descriptive and retrospective study was conducted, based in a spontaneous report system. Participants were all the patients from the IAD, with suspected ADR, reported to NPC by specialists after the study was completed. Results: Studied population had a median age of 41 years, with the predominance of the female gender (73.2%). Allergic rhinitis and asthma were the most frequent comorbidities. All studied ADR were type B, 89.6% were serious, 86.4% unexpected and 2.6% associated with drugs that presented less than 2 years in the market. The most represented drug classes were the non-steroidal anti-inflammatory drugs (NSAIDs) (52.6%) and antibiotics (25.2%). Skin symptoms represented 61.2% of the reported complaints. About 52.9% of these ADR occurred in less than one hour after intake. The most frequent ADR treatment at the time of the reaction was drug interruption (86.2%), followed by the prescription of anti-histamines (42.2%). Conclusions: Reported ADR to NPC by the Drug Alert Unit were mainly serious, unexpected, associated with NSAIDs and antibiotics and related with marketing authorization medicines older than two years. These results could be very useful to develop strategies to prevent the clinical and economic consequences of ADR.